2001
DOI: 10.1046/j.0016-8025.2001.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to cavitation of leaf minor veins: any impact on leaf gas exchange?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
94
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 45 publications
12
94
3
3
Order By: Relevance
“…8E-H). Increases K leaf with increasing temperature and light have been previously reported for several species (Holbrook et al, 2001;O'Brien et al, 2004;Salleo et al, 2001;Voicu et al, 2008). The increase of K leaf was observed in previously water-stressed plants following rainfall.…”
Section: Response Of Sap Flow To Water Potential and K Leafmentioning
confidence: 61%
See 3 more Smart Citations
“…8E-H). Increases K leaf with increasing temperature and light have been previously reported for several species (Holbrook et al, 2001;O'Brien et al, 2004;Salleo et al, 2001;Voicu et al, 2008). The increase of K leaf was observed in previously water-stressed plants following rainfall.…”
Section: Response Of Sap Flow To Water Potential and K Leafmentioning
confidence: 61%
“…The threshold was identified as the lowest rainfall event to be significantly different from the 0-5 mm rainfall class (Statistica version 8), conceptually similar to a method commonly used in ecotoxicology studies to identify the lowest observed effect concentration (Salleo et al, 2001). Data were excluded for the following situations, to comply with the characteristics of a rainfall pulse: when rainfall events lasted longer than 5 days or interpulse periods lasted less than 1 week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one has to be cautious when using this method, because the filtering has a strong effect on the estimated vulnerability. Other arbitrary methods include setting the endpoint at a water potential value that equals (i) the endpoint taken from parallel testing with another method [77]; (ii) a value taken from literature; or (iii) the turgor loss point of the leaves [78,79].…”
Section: Endpoint Selectionmentioning
confidence: 99%